2007
DOI: 10.1038/sj.jhh.1002212
|View full text |Cite
|
Sign up to set email alerts
|

Increased consumption of fruit and vegetables is related to a reduced risk of coronary heart disease: meta-analysis of cohort studies

Abstract: Increased consumption of fruit and vegetables has been shown to be associated with a reduced risk of coronary heart disease (CHD) in many epidemiological studies, however, the extent of the association is uncertain. We quantitatively assessed the relation between fruit and vegetable intake and incidence of CHD by carrying out a meta-analysis of cohort studies. Studies were included if they reported relative risks (RRs) and corresponding 95% confidence interval (CI) of CHD with respect to frequency of fruit and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

18
433
1
12

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 631 publications
(464 citation statements)
references
References 46 publications
18
433
1
12
Order By: Relevance
“…FV intake was significantly associated with both ischaemic and haemorrhagic stroke (20) . Dauchet et al (19,21) carried out their analyses differently from He et al (18,20) , calculating the RR per portion increase in FV intake. For CHD, nine studies were included (221 080 individuals; 5007 CHD events; range of follow-up 5-19 years).…”
Section: Ecological/modelling Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…FV intake was significantly associated with both ischaemic and haemorrhagic stroke (20) . Dauchet et al (19,21) carried out their analyses differently from He et al (18,20) , calculating the RR per portion increase in FV intake. For CHD, nine studies were included (221 080 individuals; 5007 CHD events; range of follow-up 5-19 years).…”
Section: Ecological/modelling Studiesmentioning
confidence: 99%
“…Individual prospective cohort studies published since the meta-analyses (18)(19)(20)(21) have tended to confirm the association (22)(23)(24)(25)(26)(27)(28) , although these studies do vary in terms of the dietary assessment and statistical analysis methodology used. Within these later studies there has also been some inconsistency in terms of whether it is total FV intake that is associated with reduced CHD risk, or fruit or vegetables alone (22)(23)(24) or specific classes of FV (26) .…”
Section: Ecological/modelling Studiesmentioning
confidence: 99%
“…Epidemiologic studies have shown that high consumption of fruits and vegetables reduces the risk for common causes of death (Lock et al 2005;He et al 2006aHe et al , 2007 and improves cognitive performance in healthy elderly people (Polidori et al 2009;Nurk et al 2010). Previous research from our laboratory, and several others, suggests that the combinations of antioxidant/antiinflammatory phytochemicals found in fruits and vegetables may effectively combat some of the effects of aging [see Miller and Shukitt-Hale (2012) for a review of these studies].…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological data support consumption of fruits and vegetables in the reduction of cardiovascular risk (1)(2)(3)(4)(5) leading to supportive recommendations by the World Health Organisation (6), European Society of Cardiology (7) and jointly the American College of Cardiology and American Heart Association (8). Many components may contribute to benefits including potassium, non-starch polysaccarides, carotenoids, vitamin C and E and phenolic compounds with bioactive phytochemical constituents having a C 6 -C 3 -C 6 flavonoid structure.…”
Section: Introductionmentioning
confidence: 99%